The blend of poetry and document in the photographical artist’s book The Road is Wider than Long by Roland Penrose (1939) - Anne Reverseau (Interfaces)
The Road is Wider than Long is a paradoxical artist’s book created by Roland Penrose in 1939. At the same time documentary and poetic, a travel report and a lyrical production, it comprises free verse, typographic poetry, “papiers collés”, and photographs. This heterogeneous nature allows to explore the contrasts and contradictions between but also the coming together of avant-garde poetry and photography. First, this article shows how The Road is Wider than Long draws from amateur practices by focusing on Penrose’s method of handling the pictures. Then, turning to the actual text, it elaborates on the notion of “poetic rendition”. Finally, it discusses the power of poetry when it is interwoven with and combines different aesthetics and intentions, and this at the crossroads of memory and document. Originally a keepsake to keep a record of a couple’s trip memories in the Balkans, The Road is Wider than Long belongs at the same time to Surrealist books with photography illustrations and to the tradition of the photobooks focused on territories.